AI AS A VIRTUAL TUTOR: THE IMPACT OF CONVERSATIONAL AGENTS ON ENGLISH LANGUAGE PROFICIENCY - Rajabova Niginaxon Raxmatullayevna; Usmonova Dona Satvoldiyevna (Western European Studies, 2025)
The integration of artificial intelligence (AI) into education has opened up innovative avenues for language learning, especially in mastering English as a second language. In particular, conversational agents — AI-powered virtual tutors — have emerged as effective tools in this process. These agents simulate human interaction and provide learners with opportunities to practice and improve their language skills outside traditional classroom settings.
Keywords: AI; education; virtual tutors